Public Sectors in the Pacific Islands : Are They 'Too Big' and Do They 'Crowd Out' the Private Sector? - Horscroft, Virginia (World Bank Group, Washington, DC, 2014)
Public sectors in the Pacific Islands are frequently described as being 'too big' and as 'crowding out' private sector economic activity. Reducing their size, it follows, would provide much-needed space for private sector expansion and result in higher levels of economic growth. This paper addresses these issues, arguing that there is not a good case for supposing that public sectors in the Pacific Islands are excessively large, when the challenges of public administration and public service delivery in such small, remote, dispersed, and divided states are taken into account. Rather than being preoccupied with their size, it would be more useful to focus on whether the resources available to their public sectors are being used efficiently and effectively to provide an adequate range and quality of administrative functions and public services. The paper also argues that, at a general level, the case for crowding out in the Pacific Islands is not particularly compelling, and that it would be more useful to focus on the trade-offs for the private sector of public sector engagement in any given administrative function or area of service delivery. In light of the arguments put forward, the paper sets out the key elements of a refocused agenda on public sector reform in the Pacific Islands.